PAHAM KEAGAMAAN MASYARAKAT DIGITAL (KAJIAN ATAS DAKWAH USTADZ ABDUL SOMAD PERSPEKTIF KONSTRUKSI SOSIAL) - Salman Zahidi; Hepi Ikmal (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
Religion which was originally in the realm of real reality, must now be included in the realm of virtual reality which clearly has very different characteristics. This new reality is characterized by simulation, artificiality, immersion, networked communication, and telepresence. Through a study of social media followers of Ustadz Abdul Somad (UAS), this study seeks to raise a number of fundamental questions, including: 1) how is the construction of religious understanding of followers of the social media account of UAS? 2) What are the models of religious understanding of UAS followers? 3) How is the content of UAS lectures on social media that provoke the pros and cons of religious understanding as a new religious authority ?. By using qualitative research methods through content analysis, and adopting the social construction paradigm developed by Peter L. Berger, this study produced several findings: First, the expression of religious ideas in the official account of Ustadz Abdul Somad, whether in the form of agreement or not, not rarely done using a variety of ways, ranging from rude statements, appreciative, and even intimidating. Secondly, the virtual society understanding model gives rise to a more open and free pattern of religious understanding. Third, free interaction in this virtual world in turn can lead to a more open attitude in dealing with differences. Fourth, free religiousinteraction hasimplications forreligious discourse as if without any restrictions. Variousreligious understandings meet in a virtual world without anyone being ableto control.